Ali asked in Science & MathematicsMathematics · 4 weeks ago

# What are the coordinates of D?

A. (3,-8)

B. (2,6)

C. (6,-13)

D. 12

Relevance
• 4 weeks ago

Apply the midpoint formula:

.............x1 + x2..........y1 + y2

mid = (--------------, ----------------)

.................2.....................2

given midpoint (4,-5) and C(2,3)

solving for x

.......2 + x

4 = ---------

...........2

8 = 2 + x

8 - 2 = x

x = 6

solving for y

...........3 + y

- 5 = -----------

...............2

- 10 = 3 + y

- 10 - 3 = y

y = - 13

Therefore, the coordinates of D is (6,-13)..

• Philip
Lv 6
4 weeks ago

M(4,-5) is the midpoint of CD, where C=(2.3) & D=(x,y).;

Then (4,-5) = (1/2)(x+2,y+3);

ie., 2(4,-5) = (x+2,y+3);

ie., (8,-10) = (x,y) + (2,3);

ie., (8,-10)-(2,3) = (x,y);

ie., (x,y) = (8-2,-10-3) = (6,-13).;

• 4 weeks ago

Let D=(x,y), then

(x+2)/2=4

(y+3)/2=-5

=>

x=6

y=-13

• 4 weeks ago

M is the midpoint of the line CD.

If the midpoint M is (4, -5) and C is (2, 3),

then the coordinates of D are (6, -13).

A. (3, -8)

B. (2, 6)

D. 12

• 4 weeks ago

C (2 ; 3)

D (xD ; yD)

The midpoint of CD is the point M (4 ; - 5)

xM = (xC + xD)/2

4 = (2 + xD)/2

8 = 2 + xD

xD = 6

yM = (yC + yD)/2

- 5 = (3 + yD)/2

- 10 = 3 + yD

yD = - 13

→ D (6 ; - 13)

• 4 weeks ago

Let (x, y) be the coordinates of D.

The coordinates of M:

((2 + x)/2, (3 + y)/2) = (4, -5)

The x-coordinate of M:

(2 + x)/2 = 4

2 + x = 8

x = 6

The y-coordinate of M:

(3 + y)/2 = -5

3 + y = -10

y = -13

Hence, the coordinates of M = (6, -13)

• 4 weeks ago

From 2 to 4 --> (add 2) --> 4 to 6

From 3 to -5 --> (subtract 8) --> -5 to -13

C. (6,-13)

• David
Lv 7
4 weeks ago

The coordinates of D are (6, -13)

• 4 weeks ago

The midpoint can be found by finding the means of the x and the y coordinates.

D is unknown so I'll call that (x, y)

We are then told that the point (4, -5) is the midpoint between (2, 3) and (x, y)

Using this information we can solve for x and y.

Midpoint's x is the mean of the endpoint's xs:

(2 + x) / 2 = 4

2 + x = 8

x = 6

Midpoint's y is the mean of the endpoint's ys:

(3 + y) / 2 = -5

3 + y = -10

y = -13

So the other endpoint (point D) is (6, -13) (answer C).